Pengaruh Kualitas Laporan Keuangan Terhadap Kinerja Usaha UMKM - Yunita Eriyanti Pakpahan (Universitas PGRI Madiun, 2021)
The small and medium business sector (SMEs) is one of the axis of the rise of the national economy that has problems in applying accounting in accordance with SAK ETAP. The role of SAK ETAP in providing information about the effectiveness and efficiency of a business's economic activities. The purpose of this study is to analyze the effect of the quality of financial statements on MSMEs business performance. Data from this study were obtained from a questionnaire with respondents of MSMEs entrepreneurs in the city of Medan. The number of respondents is 100 who are MSME entrepreneurs. The data obtained was then analyzed using SPSS. The results of this study indicate that the quality of financial statements has a significant effect on SMEs business performance.Keyword: Financial Statement’s Quality; Performance; MSMEs